Strategi Pengembangan Wilayah Ekonomi Berbasis Komoditas Pala Pada Kabupaten Fakfak Papua Barat - Sriwijaya, Reski rahman (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to identify and analyze the development strategy of local economic areas based on nutmeg commodities in Fakfak Regency through a descriptive approach with SWOT analysis. The results of the study revealed that the optimization of nutmeg cultivation in the region is supported by a number of strength factors, such as the suitability of geographical conditions, farmers' experience in managing nutmeg plants, and competitive product quality. In addition, the availability of abundant natural resources is a strategic potential in the development of this sector. However, the study also identified a number of challenges, especially related to limited human resources and minimal knowledge of nutmeg development techniques, which have implications for obstacles in the distribution of agricultural products. Thus, this study provides comprehensive insight into the potential and obstacles in the development of nutmeg-based economic areas in Fakfak Regency, and offers strategies that can optimize production and distribution efficiency in order to increase the competitiveness of the nutmeg agricultural sector in the region.